VD_FINDINFO Jug / 2015 / 54 vom 9. Oktober 2014 - VD Tribunal cantonal (2014)
JUGEMENT PAR DÉFAUT, DÉFAUTCONTUMACE, DROIT D'ÊTRE ENTENDU | 3 al. 2 let. c CPP (CH), 367 al. 1 CPP (CH), 368 al. 3 CPP (CH)